(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
Ciabòt Cagna (Piedmont, NW Italy) is a post-evaporitic Messinian fossiliferous locality. According to the literature, in Ciabòt Cagna was recorded the ochotonid Prolagus michauxi, but the present revision led to: 1) ascribe it to Prolagus sorbinii, a species present since the beginning of Messinian in continental Italy; 2) exclude a W Europe immigration source of ochotonids into continental Italy during Messinian; 3) and modify the geographical range of P. sorbinii and P. michauxi, which boundary should be W Alps.